Analysis of the preparation of financial reports on village unit cooperatives (kud) thanks to sustainable Beringin village sustainable Kampar district - Mariyah Mariyah (Institute of Accounting Research and Novation (IARN), 2023)
This research was conducted at the Beringin Lestari Village Cooperative (KUD) Beringin Lestari, Tapung Hilir District, Kampar Regency. The purpose of this study was to find out whether the preparation of the Village Unit Cooperative Financial Statements (KUD) of Berkat Lestari is in accordance with SAK, the data used is primary data, namely data obtained directly from cooperative management and cooperative employees regarding business activities and the history of cooperative development and data secondary, namely cooperative reports including balance reports, reports on the calculation of the remaining results of operations, cash flow reports and organizational structures. This study uses a descriptive method, which is a way of analyzing by comparing existing data with the theory that has been obtained.